The SUPERankle procedure in the treatment of foot and ankle deformities in fibular hemimelia - Fraga, Carlos Eduardo Cabral; Souza, Gabriel João Francisco; Martins, Jefferson Soares; Souto, Marcos Vinicius Muniz Lemos; Pinto, Rodolfo Amoedo de Castilho Candido; Chaves, Túlio Romano Troncoso (Journal of the Foot & Ankle, 2021)
Objective: To review indications for limb amputation or reconstruction using the SUPERankle procedure in patients diagnosed with Paley type 3 or 4 fibular hemimelia; To evaluate the correction of deformities needed to achieve a stable plantigrade foot, review variations of the original technique and their applicability, and describe challenges encountered in their execution. Methods: Qualitative, retrospective, descriptive study of 4 patients who underwent the SUPERankle procedure between 2019 and 2020 for treatment of foot and ankle deformities in fibular hemimelia. Pre- and postoperative clinical and radiographic evaluations were performed to identify objective evidence of the correction of foot and ankle deformities. The operative techniques employed are described. Results: The included patients met anatomical and psychosocial criteria for reconstruction, as established in the literature. Clinical correction of foot and ankle deformities was achieved, but on radiographic evaluation, there was no statistical difference; this was likely due to the small number of patients, given the rarity of fibular hemimelia. Conclusion: The procedure is reproducible, but requires a knowledgeable, well-trained surgical team. Correction of foot and ankle deformities can be achieved. The choice between amputation or reconstruction should be the result of an informed decision by Family members, supported by a multidisciplinary team. Level of Evidence IV; Qualitative Study; Case Series.